Load-Balancing Based On Geographic Routing Around Connectivity Holes In Wireless Sensor Network (International Journal of Engineering and Computer Science, 2017)
To detecting connectivity failure around the wireless sensor network by using Adaptive Load-Balancing Algorithm (ALBA) for find the solution to identify the localization errors. Rainbow mechanism is used to differentiate grouping sensor nodes by various colors. Both Adaptive Load-Balancing Algorithm and Rainbow mechanism (ALBA-R) are detects connectivity holes in network, a protocol for converge casting in wireless sensor networks. ALBA-R features are used in existing system for detecting localization error in the sensor network. Information can be gathered from node location; during end to end transmission of data packet loss will occur because of traffic in the transmission path. Even though connectivity failure occurred in wireless sensor network should increases the path cost of data transmission. To Propose Hole Healing algorithm to identify and heal holes in the network. The hole detection mechanism is used to solve the connection failure in between sensor nodes. The limited numbers of nodes neighboring the hole, only those nodes are involved in the process of moving and repairing the hole. Implementing Hole Healing Algorithm by using ns-2 simulation, for increasing performance by finding Localization error and solving those problems.